Pengaruh Skincare Berbasis Nanoemulsi terhadap Penyerapan Zat Aktif di Kulit - Parvez, Sabita Lutfun Nisa Ramdhini (Maliki Interdisciplinary Journal, 2025)
The advancement of nanotechnology in skincare formulation offers new opportunities to enhance the delivery of active ingredients into the skin. Nanoemulsions with droplet sizes ranging from 20 to 200 nm, improve solubility, stability, and penetration of active compounds through the stratum corneum, which is the main barrier to topical absorption. This literature review aims to analyze the effect of nanoemulsion-based skincare on the absorption of active ingredients into the skin based on national and international studies. The findings indicate that research in Indonesia has successfully formulated nanoemulsions with particle sizes below 200 nm, showing good stability and biological activities such as antioxidant, anti-aging, and hair growth stimulation. However, most local studies remain limited to physical characterization without direct skin penetration tests. In contrast, international studies have more frequently incorporated both in vitro and in vivo evaluations to measure penetration and bioavailability. Therefore, nanoemulsions hold great potential as a delivery system for active compounds in skincare, but further research is needed to assess actual skin penetration and long-term safety.